The Implementation of Differentiated Instruction and Adaptive Assessment in Improving English Reading Comprehension in an Efl University Context - Ega Melani; Helta Anggia; Helta Anggi (Journal of English Language and Education, 2026)
This study investigates the implementation of differentiated instruction and adaptive assessment in improving the reading comprehension of university students in an English as a Foreign Language (EFL) environment. Both approaches have been recognised widely for their pedagogical benefits, but they are rarely employed simultaneously, which is a missed opportunity for a more holistic approach to instructional design. Moreover, there is a lack of study on the implementation of adaptive evaluation in different EFL reading teaching. To overcome this gap, an eight-session mixed-methods intervention was administered to 20 first-semester university students enrolled in an intensive reading course. The quantitative data were analysed using t-tests and Rasch modelling and the qualitative data were collected using classroom observations and semi-structured interviews. Results showed statistically significant gains in reading comprehension. Rasch analysis further evidence of consistent levels of learner competency and meaningful development among participants. Furthermore, the students found the adaptive assessments fair and transparent, which increased their engagement and awareness of their learning progress. Overall, the findings suggest that the use of differentiated instruction and Rasch-based adaptive assessment is an effective way to support reading development by aligning instructional delivery and assessment practices to learners’ needs.